Problemas de mezclado y uniformidad en la industria de alimentos para animales - Vargas González, Emilio (2013)
Mixing and uniformity issues in the feed industry. This paper discuss the main issues related with proper mixing and feed uniformity on animal performance. An analysis is made of the factors that contribute to non-uniformity such as ingredient characteristics, insufficient mix time, mixer overload, worn on broken mixing components, ingredient build-up, improper sequence of ingredient addition among others. The main part of the paper is focus to diet uniformity and its effect on animal performance. The present-day information shows that coefficient of variation (CV) of growing animals are probably less sensitive to diet non uniformity that once thought, with a CV (Quanta as chromium analysis) of 72%bengadequate for broiler chicks and nursery pigs and a CV of at least 15% (and probably higher) being adequate for finishing pigs. At present, there is no "standard" testing procedure that gives accurate results on mixers performance. It is need to design new procedures and conduct credible research that will result in a better understanding of the value of uniformity and the cost of non-uniformity in livestock production. Howeve4 commercial feed manufactures still should exercise care to provide uniformity in diets that have feed additives, such as antibiotics, that are subject to testing by regulatory agencies, and the satisfaction obtained in producing quality feeds.